2002
DOI: 10.1210/endo.143.4.8719
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Proteins Stimulate Angiogenesis through Osteoblast-Derived Vascular Endothelial Growth Factor A

Abstract: During bone formation and fracture healing there is a cross-talk between endothelial cells and osteoblasts. We previously showed that vascular endothelial growth factor A (VEGF-A) might be an important factor in this cross-talk, as osteoblast-like cells produce this angiogenic factor in a differentiation-dependent manner. Moreover, exogenously added VEGF-A enhances osteoblast differentiation. In the present study we investigated, given the coupling between angiogenesis and bone formation, whether bone morphoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 497 publications
(76 citation statements)
references
References 41 publications
4
58
0
1
Order By: Relevance
“…During bone formation and fracture healing there is a crosstalk between endothelial cells and osteoblasts. VEGF has been proved to be an important factor in this cross-talk [39]. This study suggested that VEGF might be involved directly in bone formation.…”
Section: Discussionmentioning
confidence: 74%
“…During bone formation and fracture healing there is a crosstalk between endothelial cells and osteoblasts. VEGF has been proved to be an important factor in this cross-talk [39]. This study suggested that VEGF might be involved directly in bone formation.…”
Section: Discussionmentioning
confidence: 74%
“…[70,71] Osteogenic growth factors produced by ECs (BMP-2, PDGF-BB) and by osteoblasts (insulin-like growth factor, IGF, and transforming growth factor, TGF) also have an angiogenic effect by inducing VEGF mRNA expression in osteoblasts. [70,[72][73][74] Veillette and Schroeder [75] proposed an inhibitory role of ET-1 on VEGF synthesis in osteoblastic cells as a feedback mechanism in the temporal and spatial coupling of angiogenesis to bone formation and resorption.…”
Section: Heterotypic Communication Between Osteoblasts and Endotheliamentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) is among the most potent pro-angiogenic proteins, and is particularly relevant during new bone formation. [ 15 ] For example, VEGF-induced angiogenesis has recently been shown to direct bone formation at sites of endochondral ossifi cation, [ 16 ] during normal fracture healing, [ 17 ] and during bone regeneration. [ 18 ] Therefore, there is a need for materials that can locally deliver VEGF to sites of bone healing.…”
Section: A Modular Hydroxyapatite-binding Version Of Vascular Endothmentioning
confidence: 99%